"A wound that has been festering since 2007": The Burma/Myanmar naming controversy and the problem of rarely challenged assumptions on Wikipedia. Issue 4 (10th July 2017) - Luyt, Brendan
Abstract : Purpose: The Burma/Myanmar naming controversy on Wikipedia stands as an exemplary debate at least in terms of the politeness and civility of discourse. It was also one of the longer running debates on Wikipedia beginning almost at the same time as the creation of the article in 2003. But this debate has other lessons for those interested in one of the world's key pieces of information infrastructure. The paper aims to discuss these issues. Design/methodology/approach: The author's approach to the study of the Wikipedia talk pages devoted to the Burma/Myanmar naming controversy is qualitative in nature and explores the debate over sources through textual analysis. Findings: Editors brought to their work a number of underlying assumptions including the primacy of the nation-state and the nature of a "true" encyclopedia. These were combined with a particular interpretation of neutral point of view (NPOV) policy that unnecessarily prolonged the debate and, more importantly, would have the effect, if widely adopted, of reducing Wikipedia's potential to include multiple perspectives on any particular topic. Originality/value: The study clearly shows how editors tend to uncritically reproduce the dominant assumptions of their societies. When combined with positivist readings of NPOV policy, this has grave implications for Wikipedia's potential to open up representation to a wider set of knowledge producers and perspectives. Much of this potential cannot be realized if the assumptions of editors, especially their flawed understanding of NPOV, cannot be challenged effectively.